Microbiological Assessment of Fresh Expressed Breast Milk on Room Temperature at Dr. Soetomo Hospital Neonatal Unit - Widjaja, Nur Aisyah; Hardiyani, Kartika; Hanindita, Meta Herdiana; Irawan, Roedi (Folia Medica Indonesiana, 2019)
Storing EBM at room temperature in several hours before consuming, frequently found in Indonesia. Based on Academy of Breastfeeding Medicine guidelines EBM can last for 6 to 8 hours in room temperature (25oC or 77oF). However, currently there hasn't been study in tropical country especially Indonesia for the guidelines. This study aimed to assess microbiological quality of EBM on room temperature, including bacterial growth and major bacterial found on EBM for health care and society recommendations. An observational study of 30 expressed breast milk samples provided by 30 healthy women with term baby below 6 month old. The samples were kept sterile and laid at plates for 0 hours, 2 hours, 4 hours and 6 hours in room temperature (26°-32° C) and used drop plate technique on several culture media. Data was analyzed by Chi-square and paired sample T-test. Thirty of unheated fresh EBM from 30 lactating mothers were stored at room temperature, examined for the degree of bacterial contamination at 0 hour, 2 hours, 4 hours, and 6 hours. All the EBM samples were contaminated at 2 hour. Bacterial species identified was Coagulase-negative Staphylococcus (CNS), Escherichia coli, Klebsiella pneumoniae and Streptococcus faecalis, range of growth 109 cfu/ml-63 x 109 cfu/mm3 after 6 hour of storage. The EBM exposed at room temperature (30-36 0C) for more than two hour reduce the quality and do not recommended to be given to the infants.